PENGEMBANGAN RPP MATEMATIKA DENGAN PERFORMANCE STRATEGY BERBASIS KARAKTER PADA MATERI BANGUN RUANG KELAS VIII - Nurmaidah, Nurmaidah; Afriyani, Dona; Trisoni, Ridwal (Jurnal Pembelajaran MIPA, 2014)
This research is aimed to produce math lesson plan by using performance strategy as teaching strategy and fulfill characterized lesson plan which is valid and practical to be used in the field. This research is developmental research that uses modification type 4-D several steps define, design, and develop (disseminate is discarded). Collecting the data in this research was done by validating through several experts and discussion, interview, questionnaire, and observation. Technique of data analysis in this research is descriptive statistics. Result of the research showed that lesson plan that has been revised fulfilled valid criteria. Interview and answering questionnaire showed that the lesson plan is practical to be used. In conclusion, validity and practicality of the lesson plan was achieved.Kata kunci: lesson plan, performance strategy, character